2010
DOI: 10.2353/ajpath.2010.091021
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Increases the Expression of Stem-Cell Markers and Promotes Clonogenicity in Glioblastoma Neurospheres

Abstract: Hypoxia promotes the expansion of non-neoplastic stem and precursor cell populations in the normal brain, and is common in malignant brain tumors. We examined the effects of hypoxia on stem-like cells in glioblastoma (GBM). When GBM-derived neurosphere cultures are grown in 1% oxygen, hypoxia-inducible factor 1␣ (HIF1␣) protein levels increase dramatically, and mRNA encoding other hypoxic response genes, such as those encoding hypoxia-inducible gene-2, lysyl oxidase, and vascular endothelial growth factor, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
293
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(320 citation statements)
references
References 78 publications
(68 reference statements)
19
293
0
Order By: Relevance
“…It has been previously reported that Notch signaling is elevated during hypoxia (8,10,11,14,18). Here we show that a substantial part of this elevation can be attributed to increased expression of the Notch ligand JAG2.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It has been previously reported that Notch signaling is elevated during hypoxia (8,10,11,14,18). Here we show that a substantial part of this elevation can be attributed to increased expression of the Notch ligand JAG2.…”
Section: Discussionsupporting
confidence: 54%
“…Several mechanisms have been proposed including direct icN1 stabilization by interaction with HIF proteins (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). As of yet, little attention has been given to Notch ligand regulation and the effects this may have on Notch activation under hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies revealed that cellular stresses like drug exposure (Chua et al, 2008;Calcagno et al, 2010;Fong et al, 2010), hypoxia (Bar et al, 2010) and UV lighting (Liang et al, 2010) enriched for a CSC phenotype in cancer cell lines. In this study, we detected 1% cells positive for SP in the primary line SW1116 and observed a remarkable increase to 6%, 44% and 97% after HCPT treatment to 3 months, 6 months and 41 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence additionally support a direct and crucial role for cancer stem cells in the recruitment, expansion and differentiation of normal host-derived tumor vasculature, thereby contributing to another well-documented intratumoral heterogeneity ( (Pietras et al, 2008;Kim et al, 2009;Li et al, 2009;Bar et al, 2010;Mendez et al, 2010;Pietras et al, 2010;Pistollato et al, 2010a;Seidel et al, 2010). The mechanisms underlying this pseudo-hypoxic phenotype of cancer stem cells remain poorly understood, but it is increasingly clear that both metabolic and angiogenic heterogeneity within tumors are affected by aberrant expression of key players of the hypoxic response.…”
Section: Cancer Stem Cells In Angiogenesismentioning
confidence: 99%
“…This is particularly true perhaps for the Notch signaling pathway, that has emerged as a popular target in tumor biology both for targeting stem cell phenotypes and aberrant tumor vascularization (Gustafsson et al, 2005;Zeng et al, 2005;Noguera-Troise et al, 2006;Ridgway et al, 2006;Siekmann and Lawson, 2007;Thurston et al, 2007;Bar et al, 2010;Charles et al, 2010;Pistollato et al, 2010b;Yustein et al, 2010). Indeed, there is accumulating evidence that the pseudo-hypoxic phenotype of cancer stem cells itself will lead to increased Notch signaling or specific expression of elements of the Notch signaling pathway, subsequently leading to an increase in both tumor "stemness" and tumor vascularization (Jögi et al, 2002;Gustafsson et al, 2005;Sahlgren et al, 2008;Chen et al, 2010;Eliasz et al, 2010;Pietras et al, 2011).…”
Section: Cancer Stem Cells In Angiogenesismentioning
confidence: 99%